Impact of Urine Sterility on the Extent of Bacterial Colonization in Patients with Forgotten DJ Stents - Waqar Haider, Syed Muhammad; Jamil, Sana; Shehzad, Asad; Haneef, Faisal; Rizvi, Adib ul Hassan (Indus Journal of Bioscience Research, 2025)
Objective: To determine whether pre-removal urine sterility predicts bacterial colonization of double-J (DJ) stent tips in patients with forgotten stents (>4 months), and to describe organism distribution and antimicrobial susceptibility. Methods: A comparative cross-sectional study was conducted over five months in the Department of Urology, Sindh Institute of Urology and Transplantation, Karachi. Adults (18–60 years) with indwelling DJ stents >4 months were enrolled using consecutive sampling. Patients with recent antibiotics (within four weeks), known pre-stent UTI, immunocompromised, or no pre-removal urine culture were excluded. Midstream urine (CLED agar) was obtained before removal; the distal 3 cm of each stent (Chocolate and MacConkey agars) was cultured at removal. Identification and susceptibility followed standard methods and CLSI 2024. Descriptive statistics were generated; the association between urine sterility and colonization was assessed with chi-square. Results: Sixty-five patients were included (mean age 39.4±6.7 years; 57% male). Mean stent dwell time was 6.7±1.8 months. Urine was sterile before removal in 28 (43%). Stent colonization occurred in 55 (85%). Among those with non-sterile urine, 34/37 were colonized; among those with sterile urine, 21/28 were colonized (χ² p=0.064). Gram-negative organisms predominated: Klebsiella pneumoniae (18.2% of all isolates), Enterobacter cloacae (16.4%), Escherichia coli (14.5%), Proteus mirabilis (12.7%), Acinetobacter baumannii (10.9%), and Pseudomonas aeruginosa (3.6%). Gram-positive isolates included Staphylococcus aureus (10.9%), Staphylococcus epidermidis (7.3%), and Enterococcus faecalis (5.5%). Gram-negative susceptibility was highest to imipenem (91%) and meropenem (74%), intermediate to cefoperazone-sulbactam (71%), piperacillin-tazobactam (62%), and amikacin (62%), and lowest to ampicillin (17%) and amoxicillin-clavulanate (29%). Gram-positive isolates were uniformly susceptible to vancomycin and linezolid (100% each). Conclusion: Pre-removal urine sterility did not reliably exclude stent colonization, which remained high in forgotten stents. Stent-tip cultures and culture-directed therapy should guide management alongside timely stent exchange/removal.